1995
DOI: 10.1128/iai.63.3.1004-1012.1995
|View full text |Cite
|
Sign up to set email alerts
|

In vivo growth characteristics of leucine and methionine auxotrophic mutants of Mycobacterium bovis BCG generated by transposon mutagenesis

Abstract: Insertional mutagenesis in Mycobacterium bovis BCG, a member of the slow-growing M. tuberculosis complex, was accomplished with transposons engineered from the Mycobacterium smegmatis insertion element IS1096. Transposons were created by placing a kanamycin resistance gene in several different positions in IS1096, and the resulting transposons were electroporated into BCG on nonreplicating plasmids. These analyses demonstrated that only one of the two open reading frames was necessary for transposition. A libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(87 citation statements)
references
References 41 publications
(40 reference statements)
5
81
0
1
Order By: Relevance
“…The possible application of these compounds as antibiotics has been speculated since the infected bacteria could uptake amino acids from their host although these compounds blocked the biosynthetic pathway of infected bacteria. However, reduced infectivity of the leucine auxotrophic strains of Mycobacterium bovis (BCG) in mice [19] suggested that the biosynthetic pathway of branched-amino acids provides novel targets for the development of antibiotics, especially for the anti-tuberculosis agents. The recombinant M. tuberculosis AHAS large subunit was sensitive to sulfonylurea derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The possible application of these compounds as antibiotics has been speculated since the infected bacteria could uptake amino acids from their host although these compounds blocked the biosynthetic pathway of infected bacteria. However, reduced infectivity of the leucine auxotrophic strains of Mycobacterium bovis (BCG) in mice [19] suggested that the biosynthetic pathway of branched-amino acids provides novel targets for the development of antibiotics, especially for the anti-tuberculosis agents. The recombinant M. tuberculosis AHAS large subunit was sensitive to sulfonylurea derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli DH5K cells, used as cloning hosts, were grown on Luria-Bertani (LB) agar or broth supplemented with 50 Wg ml 3I kanamycin. The conditionally replicating (temperature sensitive) recombinant mycobacteriophage phAE94 [9] used to deliver the transposon Tn5367 [10] was propagated in Mycobacterium smegmatis mc P 155 at 30³C as described previously [9]. The transposon Tn5367 is a derivative of the insertion sequence IS1096 from M. smegmatis [10,12] and carries the aph gene conferring kanamycin resistance.…”
Section: Bacterial Strains Growth Conditions and Recombinant Dnamentioning
confidence: 99%
“…Chromosomal DNA was digested with EcoRI, which does not cut within the transposon, and transferred to a nylon membrane. The plasmid pYUB285 [10], which carries Tn5367, was labeled with K-[ QP P]dCTP (3000 Ci mmol 3I ) using the Rediprime DNA Labeling System (Amersham-Pharmacia) as described by the manufacturer. Hybridization and detection were done as described previously [13].…”
Section: Southern Blottingmentioning
confidence: 99%
“…Genes involved in the biosynthesis of BCAAs have also been identified as in vivo induced or essential for survival in IVET, microarray and signature-tagged mutagenesis (STM) studies in Neisseria meningitidis (ilvI, ilvD) (Sun et al, 2000), Pseudomonas aeruginosa (ilvA) (Wang et al, 1996), Pasteurella multocida (ilvD, ilvH, ilvM, yjgF) (Fuller et al, 2000;Boyce et al, 2002Boyce et al, , 2004 and Staphylococcus aureus (thrB) (Mei et al, 1997). IlvI mutants of Burkholderia mallei and Burkholderia pseudomallei (Atkins et al, 2002;Ulrich et al, 2005) and leuD mutants of Mycobacterium bovis (McAdam et al, 1995) and Mycobacterium tuberculosis (Bange et al, 1996;Hondalus et al, 2000) are attenuated. Furthermore, inhibitors of BCAA biosynthetic enzymes can prevent the growth of M. tuberculosis in the lungs (Grandoni et al, 1998;Zohar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%